2016
DOI: 10.1016/j.iac.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Rhinitis in the Elderly

Abstract: By the year 2050, the US aging population will nearly double. As the US aging population grows, it will be increasingly important for healthcare providers to effectively diagnose and manage rhinitis. The nasal symptoms of rhinorrhea, congestion, sneezing, nasal/ocular pruritus, and postnasal drainage affect up to 32% of older adults, and can significantly impact the quality of life. Several underlying factors associated with aging (such as structural changes and immunosenescence) may contribute to the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 79 publications
1
35
0
8
Order By: Relevance
“… 19 Antihistamines are effective in reducing rhinitis symptoms in the elderly, but cause adverse effects, such as urinary retention, dry mouth, constipation, arrhythmia and postural hypertension. 20 21 In the present study, total use of antihistamines tended to be lower in the treatment group than in the control group; therefore, SLIT may be beneficial for elderly rhinitis patients to reduce total medication use.…”
Section: Discussionsupporting
confidence: 42%
“… 19 Antihistamines are effective in reducing rhinitis symptoms in the elderly, but cause adverse effects, such as urinary retention, dry mouth, constipation, arrhythmia and postural hypertension. 20 21 In the present study, total use of antihistamines tended to be lower in the treatment group than in the control group; therefore, SLIT may be beneficial for elderly rhinitis patients to reduce total medication use.…”
Section: Discussionsupporting
confidence: 42%
“…In a retrospective study, Wang et al demonstrated that increasing age was associated with a decreased positivity in sIg 27 , which might be the cause of our result. Yet, other researches showed that both AR and NAR are more common among the elderly than the younger population 28,29 .…”
Section: Discussionmentioning
confidence: 92%
“…Although most reports published on the topic of aging of the nose are about nasal epithelial change, olfaction or taste, it may be deduced from previous reports that mucociliary clearance may change with aging. [7,26] The number of goblet cells decreases, resilient structures atrophy, and the basement membrane gets thicker with aging. [27] However, there is no significant agerelated change in gross or electron microscopic examination of the histopathology of the mucosa of either the septum or the turbinates.…”
Section: Discussionmentioning
confidence: 99%
“…[5] The prevalence in geriatric patients is suggested to be around 12%. [7] Epidemiologic data on rhinitis in the elderly are often neglected; however, the older population also has complaints of AR and nasal obstruction which decrease their quality of life. [8] From this point of view, studies are needed to raise the awareness of this disease in the elderly population since modern life has increased the tendency toward AR in older patients as well as in the younger age groups.…”
mentioning
confidence: 99%